Scientometric Study of Russian Research into Translation/Interpreting Pedagogy - Alikina, Elena Vadimovna; Kavardakova, Elena Leonidovna; Kushnina, Veniaminovna (International Review of Management and Marketing, 2016)
The article reviews Russian research into teaching translation/interpreting and training translators and interpreters based on the scientometric study methods. Doctoral and post-doctoral dissertations defended over the last 10 years are analyzed. The electronic catalog of the Russian State Library was used as a resource database. The papers are categorized according to the place of presentation, theme, and research lines. Approaches and concepts developed in the dissertations for the degree of Doctor of Pedagogical Sciences are outlined. Two major directions of scientific activity: modeling of pedagogical conditions for the professional development of future translators and development of didactic translation training models are characterized as the basis of translation pedagogy in Russia. The structure, spatial and temporal characteristics of its subject-object area, as well as names of the most cited authors are presented. The results allow us to identify the most active centers and schools of thought, to classify the subjects of research and to define the issues that have to be studied more profoundly. Keywords: translation, interpreting, scientometric study, dissertations, translation pedagogy JEL Classifications: N30, O30, Z00